Unraveling the chromosome 17 patterns of FISH in interphase nuclei: An in-depth analysis of the HER2 amplicon and chromosome 17 centromere by karyotyping, FISH and M-FISH in breast cancer cells (2014)
Background: In diagnostic pathology, HER2 status is determined in interphase nuclei by fluorescence in situ hybridization (FISH) with probes for the HER2 gene and for the chromosome 17 centromere (CEP17). The latter probe is used as a surrogate for chromosome 17 copies, however chromosome 17 (Chr17) is frequently rearranged. The frequency and type of specific structural Chr17 alterations in breast cancer have been studied by using comparative genomic hybridization and spectral karyotyping, but not fully detailed. Actually, balanced chromosome rearrangements (e.g. translocations or inversions) and low frequency mosaicisms are assessable on metaphases using G-banding karyotype and multicolor FISH (M-FISH) only. Methods: We sought to elucidate the CEP17 and HER2 FISH patterns of interphase nuclei by evaluating Chr17 rearrangements in metaphases of 9 breast cancer cell lines and a primary culture from a triple negative breast carcinoma by using G-banding, FISH and M-FISH. Results: Thirty-nine rearranged chromosomes containing a portion of Chr17 were observed. Chromosomes 8 and 11 were the most frequent partners of Chr17 translocations. The lowest frequency of Chr17 abnormalities was observed in the HER2-negative cell lines, while the highest was observed in the HER2-positive SKBR3 cells. The MDA-MB231 triple negative cell line was the sole to show only non-altered copies of Chr17, while the SKBR3, MDA-MB361 and JIMT-1 HER2-positive cells carried no normal Chr17 copies. True polysomy was observed in MDA-MB231 as the only Chr17 alteration. In BT474 cells polysomy was associated to Chr17 structural alterations. By comparing M-FISH and FISH data, in 8 out of 39 rearranged chromosomes only CEP17 signals were detectable, whereas in 14 rearranged chromosomes HER2 and STARD3 genes were present without CEP17 signals. HER2 and STARD3 always co-localized on the same chromosomes and were always co-amplified, whereas TOP2A also mapped to different derivatives and was co-amplified with HER2 and STARD3 on SKBR3 cells only. Conclusion: The high frequency of complex Chr17 abnormalities suggests that the interpretation of FISH results on interphase nuclei using a dual probe assay to assess gene amplification should be performed 'with caution', given that CEP17 signals are not always indicative of normal unaltered or rearranged copies of Chr17. © 2014 Rondón-Lagos et al.